2010
DOI: 10.1088/0031-9155/55/12/n02
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetry measurements with an intra-operative x-ray device

Abstract: The INTRABEAM 50 kV x-ray device can be used for intra-operative partial breast irradiation. Spherical applicators are added to the source probe to deliver a radially symmetric radiation dose. Dosimetric data for calculation of absorbed dose were measured for this unit and a superficial unit with a similar beam quality, as defined by half value layer (HVL). Chamber calibration factors, N(K), and chamber correction factors, k(ch), were determined based on HVL, according to the IPEMB code of practice and addendu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
69
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(74 citation statements)
references
References 19 publications
4
69
0
1
Order By: Relevance
“…The calculated dose value and the deviation will be very big in different tissue due to the spectrum chacteristics of the low energy photon (≤50 kV); the dose distribution will be influenced by the air gap between tissues and the applicator [14]. Monte Carlo modelling could be used in comparison with result from ionization chambers, radiochromic film and other dosimeters such as TLDs on the subsequent periodic QA tests for the INTRABEAM system [8]. There exist great difficulties for external beam radiotherapy when needed to supplement the postoperative radiotherapy especially for the accurate dose calculation and precise delineation of target and surrounding normal tissue irradiated especially for the nerves and blood vessels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The calculated dose value and the deviation will be very big in different tissue due to the spectrum chacteristics of the low energy photon (≤50 kV); the dose distribution will be influenced by the air gap between tissues and the applicator [14]. Monte Carlo modelling could be used in comparison with result from ionization chambers, radiochromic film and other dosimeters such as TLDs on the subsequent periodic QA tests for the INTRABEAM system [8]. There exist great difficulties for external beam radiotherapy when needed to supplement the postoperative radiotherapy especially for the accurate dose calculation and precise delineation of target and surrounding normal tissue irradiated especially for the nerves and blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…et al described the dosimetry of the INTRABEAM ® system with the spherical applicators [8]. Maxime Goubert et al have reported dosimetric behavior of the system equipped with flat and surface applicators [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this still ongoing trial, patients were treated with either IB‐IORT or EBRT and outcomes were compared 8. Based on this trial and other studies, IB‐IORT has shown both benefits and drawbacks as compared to EBRT.…”
Section: Introductionmentioning
confidence: 99%
“…그러나 최근에는 이러한 X선 튜 브를 작게 제작하여 다양한 부위에 적용하고자 기술 이 보고되고 있다 [2] . 표 1은 이러한 초소형 X선 튜브 의 개발 현황을 요약한 것이다 [2][3][4][5][6][7] . 이러한 초소형 X선 …”
unclassified